2010
DOI: 10.1111/j.1467-9450.2009.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid personality indicators of schizophrenia-related psychosis in a hypothetically psychosis-prone college sample

Abstract: Research into psychosis proneness has established the Chapman Psychosis Proneness Scales (CPPS), certain personality disorders, certain response patterns on the MMPI-2, and social withdrawal as being valid indicators of liability. The current study extends our understanding of premorbid indicators of schizophrenia-related psychosis (SRP) by examining whether individuals identified as hypothetically psychosis prone (HPP) by virtue of their CPPS scores also show differences on other premorbid indicators of SRP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…Solano and De Chávez, 2000;Keshavan et al, 2005;Gooding et al, 2007;Fogelson et al, 2007Fogelson et al, , 2010Bolinskey and Gottesman, 2010) demonstrating a relationship between avoidant personality disorder and liability to schizophrenia. Social withdrawal and detachment have long been noted to be a hallmark feature of liability to schizophrenia (cf.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Solano and De Chávez, 2000;Keshavan et al, 2005;Gooding et al, 2007;Fogelson et al, 2007Fogelson et al, , 2010Bolinskey and Gottesman, 2010) demonstrating a relationship between avoidant personality disorder and liability to schizophrenia. Social withdrawal and detachment have long been noted to be a hallmark feature of liability to schizophrenia (cf.…”
Section: Discussionmentioning
confidence: 96%
“…Our design allows for a direct analysis of the relationship between spectrum personality disorders and schizotypy without the influence of selection bias or demographic influence. Further, our study incorporated measures of personality disorder symptoms and personality disorder diagnoses that were obtained through semistructured interviews administered by trained clinicians and subjected to review by at least one other trained administrator, rather than relying on self-report, as in the Bolinskey and Gottesman (2010) study, or chart diagnoses that are often notoriously unreliable (cf., Garb, 1998;Jensen & Weisz, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, individuals are not indiscriminately endorsing schizotypy traits. Relatedly, individuals with psychometrically-defined schizotypy completing comprehensive measures of self-reported psychopathology (e.g., the Minnesota Multiphasic Personality Inventory) fail to produce abnormal validity profiles or elevated scores on all/most scales (Lenzenweger, 1991;Merritt, Balogh, & DeVinney, 1993;Penk, Carpenter, & Rylee, 1979) and sometimes fail to show evidence on scales presumed to tap psychosis-proneness (Bolinskey & Gottesman, 2010;Hunter, et al, 2014). Relatedly, many studies recruiting schizotypy groups also employ infrequency scales -measures that assess endorsement of infrequently occurring events, some of which have a pathological tone (e.g., "I have never combed my hair before going out in the morning"; Chapman & Chapman, 1983).…”
Section: What Might or Might Not Underlie The Subjective-objective Dmentioning
confidence: 99%
“…Those who exhibit low levels of E have a tendency to be more withdrawn. One study found that high levels of social withdrawal as measured by the Chapman Psychosis Proneness Scales (CPPS) were associated with psychotic proneness, consistent with recent literature that has found higher levels of social withdrawal in schizophrenia prodromes (Bolinskey & Gottesman, 2010). Similarly, Angst & Clayton (1986) found that within a sample of Swiss conscripts, those who later developed schizophrenia tended to score somewhat lower on E than other individuals although the difference was not significant.…”
Section: Support For Fft In Schizophreniasupporting
confidence: 59%